2013
DOI: 10.3389/fnana.2013.00030
|View full text |Cite
|
Sign up to set email alerts
|

Neurites containing the neurofilament-triplet proteins are selectively vulnerable to cytoskeletal pathology in Alzheimer’s disease and transgenic mouse models

Abstract: Amyloid-β plaque accumulation in Alzheimer’s disease (AD) is associated with dystrophic neurite (DN) formation and synapse loss in principal neurons, but interneuron pathology is less clearly characterized. We compared the responses of neuronal processes immunoreactive for either neurofilament triplet (NF+) or calretinin (CR+) to fibrillar amyloid (Aβ) plaques in human end-stage and preclinical AD, as well as in APP/PS1 and Tg2576 transgenic mouse AD models. Neurites traversing the Aβ plaque core, edge, or per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 57 publications
1
24
1
Order By: Relevance
“…The former method yielded smaller particle-size distributions, probably due both to the inclusion of objects that were not actually plaques and to underestimating the sizes of real plaques if only the plaque cores, but not the plaque peripheries, were above the threshold. Finally, yet another study [35] reported larger ThioS-positive plaques in 12-month Tg2576 and APP Swe PS1ΔE9 (gender unspecified) mice than we found here (mean areas ~ double those found in the current study). The discrepancies between the various studies point to the necessity of employing consistent methods when attempting quantitative comparisons.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The former method yielded smaller particle-size distributions, probably due both to the inclusion of objects that were not actually plaques and to underestimating the sizes of real plaques if only the plaque cores, but not the plaque peripheries, were above the threshold. Finally, yet another study [35] reported larger ThioS-positive plaques in 12-month Tg2576 and APP Swe PS1ΔE9 (gender unspecified) mice than we found here (mean areas ~ double those found in the current study). The discrepancies between the various studies point to the necessity of employing consistent methods when attempting quantitative comparisons.…”
Section: Discussioncontrasting
confidence: 66%
“…In that study, which examined the superior temporal sulcus, the ThioS plaque burden was 1.2 ± 0.2% (mean ± S.E.M., N = 62) [53]. Two smaller studies reported ThioS plaque burdens of 3.0 ± 0.3% (N = 6 [35]; N = 7 [54]) in inferior temporal gyrus. The latter study also measured ThioS plaque burdens in subjects with familial autosomal AD caused by Presenilin-1 mutations (8 subjects with 5 different mutations) and found that the burden in these subjects, 3.5 ± 0.3%, did not differ significantly from the burden in the subjects with sporadic AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Map1b is critical for microtubule stabilization during axonal growth [114] and Ntn1 plays a role in axonal guidance [81], whereas Nfh is essential in maintaining axonal caliber and is dysregulated in human AD and animal models of the disease [42, 83]. Significant downregulation of these genes suggest that LC neurons may be undergoing an axonal degenerative process during prodromal stages, which progress to frank AD as evidenced by a significant increase in the cytoskeletal proteases Capn1 and Capn2 expression in AD neurons [92, 104].…”
Section: Discussionmentioning
confidence: 99%
“…Desmin is highly expressed in muscle whereas GFAP is expressed in astrocytes. This tight regulation of IF subtype expression, which has the potential to give each cell type a “unique cytoskeletal architecture” (Chang & Goldman, ; Mitew, Kirkcaldie, Dickson, & Vickers, ), begs the question of what cell type‐specific functions the IF proteins carry out and to what degree IF proteins are functionally interchangeable.…”
Section: An Introduction To Intermediate Filamentsmentioning
confidence: 99%